(3TQM HjhY Gdabjg CHj jMji Hf LeGYI (B( (3aj Gdabg GdeGdci (B)s - (3CHh GdYHGS CMeO Hf bGSe Hf YHO GdQMef GdLPGei GdbHGHs; (3CHj jMji Hf LeGYIs ((3CHh YHO dGdg eMeO Hf YHGO s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOkG jhGab fYeg HGH GdOdjd Ydi MdjI GdHjY heG jYO UfakG ef GdWYGe bhd GdHjY LfGFR HGdcJGH hGdSfI hGdELeGY s
(3BNQgG (B:s
(3jfJgi HHGH LGeY deSGFd eNJdaI , Hbhdg ai HjY GdecGjSI aMci GdeGRQi bhdjf CMOgeG GdKdK hGdBNQ eG jbhd GdJLGQ Cfg ZHf ZjQ eYJGO GfJgi s
(3QJHg GdTGQM Ydi NeSI YTQ HGHkGs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(260 / 80) s
Keywords: (3Gdabg GdeGdcjs